Khulafa Ar Rasyidin and the Islamic Education System - Fiana Shohibatussholihah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This article will explain the educational movement and political policy in the era of the caliphs Abu Bakr As-Siddiq, Umar ibn Khattab, Uthman ibn 'Affan and Ali ibn Abi Talib. Of the four caliphs, many education systems still follow the learning model in kuttab and in mosques. The learning strategy is still strongly influenced by the teaching strategies of the Prophet Muhammad SAW first. The main teaching material is about faith in Allah, the Koran and reading and writing. Until the leadership of the caliph Ali ibn Abi Talib, new learning materials branched from fiqh material to nahwu science. With a political movement that uses a caliphate system based on proximity to the Prophet Muhammad SAW, it increasingly guarantees the authentication of Islamic religious education science so that it is far from mistakes or misguided Islamic teachings.